Efficient Production and Separation of Biodegradable Surfactants from Cellulose in 1‐Butyl‐3‐Methylimidazolium Chloride. Issue 12 (10th October 2014) - Puga, Alberto V.; Corma, Avelino
Abstract Alkyl glycoside biodegradable surfactants were produced from cellulose and 1‐octanol or 1‐dodecanol in a one‐pot, two‐step (hydrolysis–glycosidation) process in 1‐butyl‐3‐methylimidazolium chloride. Both surfactant productivity and separation efficiencies have been strikingly enhanced compared to other previously reported ionic liquid processes. Production temperatures were decreased to limit the extent of glucose dehydration and further degradation processes, but the conversions remained high. Surfactant molar yields up to 72 % were achieved by operating at 70 °C. Several separation procedures were tested to achieve high recoveries of both surfactant and ionic liquid. The use of a silica stationary phase was useful for isolation of the surfactant, whereas crystallization of the ionic liquid improved its separation efficiency. Finally, the precipitation of dodecyl glycosides in aqueous media was highly efficient for their isolation and for the recovery (>99 %) of the ionic liquid by using only water as the solvent for separation.